Characterization of students admitted during the COVID-19 pandemic in 10 de Octubre Municipality - Beatriz Fernández Prieto; Gino Iglesias Sordo; Vanesa de la Caridad Valera González; Ramiro Fidel Sanchoyerto López; Hilda Isabel Gómez Valdés (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: With the appearance of COVID-19 pandemic, medical students began to carry out active research work in Cuba. However, some of them were subjected to isolation or quarantine. Objective: To describe the clinical and epidemiological characteristics of the students admitted during the COVID-19 pandemic in 10 de Octubre Municipality. Material and Method: An epidemiological, observational, descriptive, cross-sectional study was conducted between March 18 and July 31, 2020. Non-probabilistic sampling was used in the selection of the sample, leaving 82 students admitted in the period and place under investigation. Percentages, rates and summary measures were applied. Results: Medical students represented 70.73% of the sample, of whom 65.85% were women. Sixty-seven percent were admitted to home because of indirect contact with infected people. The Luis de la Puente Uceda (LPU) Polyclinic was the area of highest global risk with an incidence rate of 81,71 per 100 thousand inhabitants. Also, 2.43% of the sample was positive for SARS-CoV-2.   Conclusions: Surveillance of indirect contacts was carried out on admission to home and positive cases were admitted to hospitals. There was minimal transmission in areas of very high global risk.  The results of the tests were negative in almost all the students. In those confirmed cases, there was no sex preference and there were no complications of the disease.